Analysis of cycle-to-cycle variations in a common-rail compression ignition engine fuelled with diesel and biodiesel fuels. (15th April 2021) - Yang, Liping; Zare, Ali; Bodisco, Timothy A.; Nabi, Nurun; Liu, Zhenting; Brown, Richard J.
Abstract: Using wavelet and fractal theories, cycle-to-cycle variations (CCVs) in a common-rail compression ignition (CI) engine have been investigated at engine loads of 25% and 50%, biodiesel blend level was from 0% to 100%. Wavelet power spectrums and singularity spectra were calculated to identify the dominant oscillatory combustion modes and multifractal complexity. Reaction paths and component consumption sensitivity of n-heptane and methyl decanoate were studied to reveal the effect of biodiesel blend level on the combustion process of diesel fuel. Results reveal that the effect of biodiesel blend level on the CCVs is more significant at a low load, even when biodiesel blend level increases to 20%, the coefficients of variation decreases from 3.99% to 1.57%. The CCVs exhibit multiscale dynamics for all tested cases, and persistent high-frequency oscillations appear around a 16-cycle period persisting over the entire or several hundred of the engine cycles. As the biodiesel blend level increases, the periodic bands with the highest power were interrupted and combined with lower-frequency and high-frequency intermittent fluctuations. However, for the higher load, the dynamics of CCVs are mainly displayed in an intermittent fashion. The larger broadness of singularity spectra at higher engine loads suggests a higher degree of multifractality. For all of the tested cases, the dynamics of the CCVs behave like antipersistent walks. As a oxygenated fuel, biofuel substitution leads to increase of c7h15-1 concentration and radicals such as OH, O and H2 O2, which are beneficial to decrease ignition delay and accelerate the chemical reaction rate of diesel fuel, and therefore inhibit the CCVs.